A-Z of neurological practice a guide to clinical neurology - Larner, A. J. (Springer, 2011)
The Second Edition of A-Z of Neurological Practice builds on the previous edition with revised and updated information in a high density but easily accessible format to provide a quick and ready reference for busy clinicians of all degrees of experience. Entries for specific neurological conditions are uniformly structured indicating: Pathophysiology; Clinical Features; Investigations and Diagnosis; Differential Diagnosis; Treatment and Prognosis. Key references are cited throughout and all entries are cross referenced. A-Z of Neurological Practice, Second Edition is a practical, authoritative.